A comparative analysis of serum phosphorus levels and mineral metabolic markers in non-dialysis and dialysis chronic kidney disease patient: a cross-sectional study - Pandit, Sanjeet Kumar; Vohra, Aditya; Mahali, Ashim Kumar; Rajendran, Karthikeyan Pandiyambakkam (International Journal Of Community Medicine And Public Health, 2023)
Background: Chronic kidney disease is a major public health problem worldwide. As kidney function declines, it leads to several metabolic abnormalities including dysregulation of mineral metabolism. It is also reported that hyperphosphatemia in patients with advanced kidney disease is associated with an increased risk of mortality and cardiovascular events, and is higher in dialysis-dependent chronic kidney disease (CKD) patients compared to non-dialysis CKD. However, data in the Indian context is limited. Objectives were to evaluate and compare serum phosphorus levels and associated factors in non-dialysis and dialysis CKD patients. Also, the impact of dietary phosphate restriction and the use of phosphate binders on serum phosphorus is analysed. Methods: A cross-sectional study was conducted at a tertiary care hospital in Kolkata, India, with 100 CKD patients: 50 non-dialysis CKD patients and 50 dialysis-dependent CKD patients. Relevant demographic, clinical and laboratory parameters including serum phosphorus, calcium, parathyroid hormone (PTH), alkaline phosphatase, albumin and estimated glomerular filtration rate (eGFR) were collected. Data was analyzed using appropriate statistical tests. Results: Mean serum phosphorus was significantly higher in the dialysis CKD group (6.12±0.34 mg/dl) compared to the non-dialysis CKD group (4.56±0.80 mg/dl). Serum calcium and PTH were also higher while eGFR and albumin were lower in the dialysis CKD group. Serum phosphorus levels increased with advancing CKD stages in the non-dialysis group. Phosphate binder helped phosphorus control in dialysis CKD patients. Conclusions: Our study is in confluence with other reports and dietary phosphate restriction and the use of phosphate binders help optimize phosphorus levels in CKD patients.